PENGARUH EKSPOR, PENANAMAN MODAL DALAM NEGERI DAN SUKU BUNGA TERHADAP PRODUK DOMESTIK BRUTO - Annisa Handayani; Tia Handani; Fidia Wati; Putri Sari Margaret Julianty Silaban; Salma Diani (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the effect of exports, domestic investment (PMDN), and interest rates on Indonesia’s Gross Domestic Product (GDP). The research uses quarterly time-series secondary data from 2017 to 2022 obtained from the Central Bureau of Statistics (BPS). The analysis method employed is multiple linear regression with the Ordinary Least Square (OLS) approach using EViews 12, supported by classical assumption tests to ensure model reliability. The results indicate that exports, domestic investment, and interest rates each have a positive and significant effect on GDP. Simultaneously, these three variables also significantly influence GDP with a contribution of 96.78%, while the remaining variation is explained by other factors outside the model. These findings highlight the importance of strengthening exports, enhancing domestic investment, and carefully managing interest rate policies to promote Indonesia’s economic growth. Keywords: Exports, Domestic Investment, Interest Rates, GDP.